The Kaldor–Kalecki stochastic model of business cycle - Mircea, Gabriela; Neamt¸u, Mihaela; Opris, Dumitru (Nonlinear Analysis: Modelling and Control, 2011)
This paper is concerned with the deterministic and the stochastic delayed Kaldor–Kalecki nonlinear business cycle models of the income. They will take into consideration the investment demand in the form suggested by Rodano. The existence of the Hopf bifurcation is studied and the direction and the local stability of the Hopf bifurcation is also taken into consideration. For the stochastic model, the dynamics of the mean values and the square mean values of the model’s variables are set. Numerical examples are given to illustrate our theoretical results.